Diagnosis and Treatment of Typical Cold-Induced Urticaria: A Case Reports - Nurul Nisa Ulfa (HM Publisher, 2023)
Background: Urticaria is a common disease in society. 15-25% of individuals must have experienced urticaria at least once in their life. Cold urticaria is included in the type of chronic inducible urticaria and is a type of urticaria that accounts for 3% of cases of all types of chronic urticaria that occur. The age group that most suffers from urticaria is the age 12-25 years. This study was aimed at presenting the diagnosis and treatment of cold urticaria. Case presentation: A 29-year-old woman came with complaints of itching and redness on the hands, feet, and neck, starting with a small round reddish rash that widened and the center was paler than the edges, then disappeared within 1-2 hours, there is no a history of infectious or autoimmune diseases but has a family history of the same complaint. Examination of the ice cube test obtained positive results after 7 minutes of contact with ice cubes. Patients were given therapy in the form of cetirizine 10 mg per day for 2 weeks, which was then increased by a dose of 20 mg with a combination of cetirizine 10 mg in the morning and loratadine 10 mg at night. Conclusion: Exploration of precipitating factors through detailed anamnesis and supporting examinations with a cold stimulation test can establish a diagnosis of typical cold-induced urticaria.